Microcapsule MOFs@MOFs derived porous "nut-bread" composites with broadband microwave absorption. (1st November 2021) - Peng, Hualong; Xiong, Zhiqiang; Gan, Zhihui; Liu, Chongbo; Xie, Yu
Abstract: Multi-composite materials with heterostructure derived from metal-organic frameworks (MOFs) have been extensively used in electromagnetic wave (EMW) absorbing applications because of their peculiar microstructure and electromagnetic characteristics. A series of Co, metal oxide semiconductor (MOS), and nanoporous carbon (NPC) composites with multi-nut-bread structure were developed by the one-step pyrolysis of capsule MOFs@MOFs, in which a surfactant assisted the fabrication of bi-MOFs constructed through different metal ions and organic ligands by an electrostatic effect. The impedance matching and attenuation ability of the absorbers were adjusted by tuning the type and content of "nuts" with different electromagnetic characteristics. The results showed that all the composites exhibited outstanding microwave absorbing (MA) performance. Specifically, the Co/ZnO/NPC-2 composite achieved the maximum reflection loss value (RLmax ) of −61.7 dB and the optimal effective bandwidth ( f e, RL ≤ −10 dB) of 5.6 GHz with a 1.88 mm thickness. The Co/ITO/NPC-2 (ITO = indium tin oxide) composite presented an RLmax of −55.1 dB at an ultra-thin thickness of 1.32 mm. In addition, an ultra-broad f e of 6.4 GHz was measured for the composite Co/TiO2 /NPC-2 with a thickness of 2.05 mm. The excellent MA performance of the composites was related to their unique multi-nut-bread structure, and the synergistic effect between the magnetic and dielectric behavior. This work provides a reliable strategy for synthesizing microcapsule MOFs@MOFs with different metal ions and organic ligands, and provides a new insight for constructing multi-interfacial ternary composites with advanced MA properties.